Mass calibration of the CODEX cluster sample using SPIDERS spectroscopy – II. The X-ray luminosity–mass relation. Issue 2 (14th April 2020) - Capasso, R; Mohr, J J; Saro, A; Biviano, A; Clerc, N; Finoguenov, A; Klein, M; Grandis, S; Collins, C; Damsted, S; Kirkpatrick, C; Kukkola, A
ABSTRACT: We perform the calibration of the X-ray luminosity–mass scaling relation on a sample of 344 CODEX clusters with z < 0.66 using the dynamics of their member galaxies. Spectroscopic follow-up measurements have been obtained from the SPIDERS survey, leading to a sample of 6658 red member galaxies. We use the Jeans equation to calculate halo masses, assuming an NFW mass profile and analysing a broad range of anisotropy profiles. With a scaling relation of the form $L_{\rm {X}} \propto \text{A}_{\rm {X}}M_{\text{200c}}^{\text{B}_{\rm {X}}} E(z)^2 (1+z)^{γ _{\rm {X}}}$, we find best-fitting parameters $\text{A}_{\rm {X}}=0.62^{+0.05}_{-0.06} (± 0.06)× 10^{44}\, \mathrm{erg\, s^{-1}}$, $\text{B}_{\rm {X}}=2.35^{+0.21}_{-0.18}(± 0.09)$, $γ _{\rm {X}}=-2.77^{+1.06}_{-1.05}(± 0.79)$, where we include systematic uncertainties in parentheses and for a pivot mass and redshift of $3× 10^{14}\, M_\odot$ and 0.16, respectively. We compare our constraints with previous results, and we combine our sample with the SPT SZE-selected cluster subsample observed with XMM–Newton extending the validity of our results to a wider range of redshifts and cluster masses.